Provision of Integrated Maternal, Newborn, and Child Health (IMNCH) Services and Its Challenges in Enugu State, Nigeria - Onunze, Regina A.; Ugbelu, Jacinta E. (International Journal of Human Kinetics, Health and Education, 2022)
Integrated maternal, newborn and child health (IMNCH) programme is designed to enhance the efficiency of health services delivered to mothers, neonates and children. The purpose of this study was to ascertain the IMNCH services provided and its challenges in Enugu State. To achieve this purpose, four specific objectives with corresponding research questions were formulated and two hypotheses postulated and tested at.05 level of significance. The study adopted descriptive survey research design. The population for the study was 2,410 health providers from which a sample of 520 was drawn using multi stage sampling procedure. The instrument used for data collection was questionnaire. Frequencies and percentages were used to answer research questions while Chi-square was used to test all the hypotheses. The findings of the study showed that outreach services (45.7%) and clinic services (40.5%) of the IMNCH programme were inadequately provided and inadequate number of staff, and misdistribution of equipment were among the challenges of services provision for IMNCH programme (94.4%) while community/family services (72.2%) were adequate. Also result showed that there was no significant difference in IMNCH services provision according to private and public health facilities while there was difference in challenges of IMNCH services provision according to private and public health facilities. Based on the findings the researcher recommended that government should bridge the challenges of IMNCH programme through distribution of drugs, equipment, training and recruitment of staff as well as creating avenue for workshops and seminars.